Eastern Europe, Central Europe, or East Central Europe? Imagined geography of the region - Leszek NOWAK (Eastern Journal of European Studies, 2022)
The aim of the article is to analyse several concepts that expressed different perceptions about the region of Central and Eastern Europe. The article proves that the choice of terminology is crucial in the discussion of the political and cultural identity of the region. The starting point is the Enlightenment concept of Eastern Europe, which suggested the backwardness and secondary status of this region. This concept is confronted with the concept of Slavophilism, inspired by Romanticism. The article argues that this idea, which initially expressed the ambitions of the region’s independence, later became an instrument of Russian imperialism. In the concept of Central Europe, as the article proves, there is a certain ambiguity: on the one hand, it contains elements of German liberal imperialism, a special role, especially economic, played by Germany in this region. On the other hand, intellectuals from this region gave the concept of Central Europe an idealized meaning that still inspires many authors writing about the region. Finally, the author analyses the concept of and East Central Europe, which is most justified by academic knowledge, but does not inspire political imagination to such an extent. In conclusion, the article refers to the relevance of some of these concepts and their interpretative potential, which depends on the current political situation.